Pengaruh Audit Delay, Fee Audit, Audit Tenure Terhadap Kualitas Audit - Shopia Aulia Tasya; Cris Kuntadi (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2024)
The purpose of writing this article is to determine the effect of audit delay, audit fees, and audit tenure on audit quality. This article was carried out by conducting a literature study from various research that has been carried out. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The results of this literature review article are: 1) Audit delay has an effect on Audit Quality, 2) Audit Eee has an effect on Audit Quality and 3) Audit Tenure has an effect on Audit Quality.